How Resilience Promotes Mental Health of Patients With DSM-5 Substance Use Disorder? The Mediation Roles of Positive Affect, Self-Esteem, and Perceived Social Support - Yang, Chunyu; Zhou, You; Xia, Mengfan (Frontiers in Psychiatry, 2020)
Objectives: The existing studies found that resilience is a salient trait which can significantly affect psychological well-being of people with substance use disorders (SUD). However, few studies examined how the mechanisms are composed between resilience and mental health among patients with DSM-5 SUD. This study investigated mediation effects of positive affect, perceived social support, self-esteem on the effect of resilience on perceived stress and life satisfaction in patients with SUD. Design: A total of 415 patients who were diagnosed with DSM-5 SUD from south of China joined the research. Outcome Measures: The study applied CD-RISC, PANAS, MSPSS, RESEPSS, SWLS to measure patients’ resilience, positive affect, self-esteem, perceived social support, perceived stress, and life satisfaction.  Results: Structural equation model analysis revealed that positive affect and self-esteem partially mediate the relationship between resilience and perceived stress, while positive affect and perceived social support partially mediate the relationship between resilience and life satisfaction. Conclusion: The findings provide insights for evidence-based substance abuse intervention that positive affect, self-esteem, and perceived social support can amplify the effects of resilience on promoting mental health of patients who are diagnosed with DSM-5 SUD.